Três ensaios sobre a política monetária brasileira no período pós metas de inflação : uma avaliação da regra de Taylor, uma estimação da taxa de juros real neutra e uma análise dos impactos do crédito direcionado - Nunes, Marivia de Aguiar (2019)
This doctoral thesis, composed of three essays whose common characteristic is the study of aspects related to the Central Bank (CB) performance after the implementation of the Inflation Target Regime (more specifically from January 2003 to May 2016, when the BC was presided over, respectively, by Henrique Meirelles and Alexandre Tombini), intends to contribute to the discussions associated with the Brazilian monetary policy, when evaluating the performance of the Institution as agent responsible for conducting monetary policy; as an agent capable of pursuing the real or structural interest rate; and as an agent that enhances the influence of monetary policy on economic activity. In the first essay, the aim is to evaluate the position of the Brazilian Central Bank as the driver of monetary policy, identifying if the Institution has followed the rule defined by Taylor (2000). After a brief review of the literature and methodology, the results of the estimation of the different reaction functions of the Brazilian Central Bank are presented. It is possible to verify in which periods and / or mandates the Institution attributed greater weight to the inflation problem of the Brazilian Central Bank. unemployment, and vice versa. The study also counts on a conjunctural analysis of the period, showing the behavior of macroeconomic variables such as GDP, per capita income, unemployment rate and consumer inflation, which is the main contribution of the work. In terms of results, it is concluded that, since the mandate of Alexandre Tombini, there was a significant change in the conduct of Brazilian monetary policy, as the CB, by being more lenient with inflation, began to attribute greater weight to the problem of unemployment rather than to inflation in its monetary policy decisions compared to that observed in the mandate of Henrique Meirelles. With regard to the conjunctural analysis, in the management of Tombini comparatively to that of Meirelles, it was observed a reduction of the rate of growth of the GDP, of the rate of growth of per capita income, increase of Country Risk, of inflation and of unemployment. In the second essay, in turn, an estimation of the neutral real interest rate of the Brazilian economy is made, a variable that, although not explicitly observable, is important in the discussions of economic policy, insofar as it denotes the "neutral" "Of a Central Bank, given that, by pursuing it, the monetary authority ensures price stability and, at the same time, exerts no influence on economic growth. In this case, the estimates were operationalized through two different methods, namely: i) use of the Hodrick-Prescott filter; and ii) a structural VAR model (SVAR). After these estimates have been made, both are combined, resulting in a single estimate for the Brazilian neutral rate. The strategy of combining the two methods was adopted because each of them has a profile and captures different information, which makes them complementary, besides returning a smoother estimate and reducing the uncertainty inherent to the estimation of a latent variable such as neutral interest, which is the main contribution of this study to the available works. The main results of this research revealed that it is not possible to affirm that the neutral interest showed a significant reduction in the period in which Alexandre Tombini was at the head of the Central Bank, suggesting that its management was marked by the discretion in the conduct of the monetary policy. Finally, in the third essay, the aim is to evaluate whether there was a reduction in the effectiveness of monetary policy after 2008, with the increase in the share of the credit balance directed in the total credit balance of the Brazilian economy, since the basic interest rate, in this interregnum, was able to act only on part of the existing credit in the economy (that is, on the free credit with market rates), which represents an important limitation of the scope of the domestic monetary policy. To do so, after a brief review of the literature and an exposition of the methodology used in this work, the estimations are performed, which are performed through a VAR model and impulse-response functions, following the procedure of Toda and Yamamoto (1995). Through this procedure and the estimated model, it is possible to verify separately the effects of the shocks of free credit and directed credit in the Brazilian monetary policy, focusing on the latter, which is the main contribution of this work in front of the others. The main results of the research revealed that, up to September 2008, the interest dynamics influenced the directed credit, which corroborates with the main hypothesis of this research, that from 2008 only free credit changes when there is change in Brazilian monetary policy. On the other hand, as of October 2008, it was verified that only free credit was influenced by monetary policy and that the directed credit dynamics negatively affected the perception of risk of the Brazilian economy in the initial periods and in longer horizons, suggesting that the policy of increasing the participation of directed credit was an event that, in the view of the markets, does not contribute to the positive evolution of the country. One of the main contributions of this thesis is that, under different prisms, of the Brazilian monetary policy after the RMI, implemented almost 20 years ago, identifying if the performance of the CB in this period has contributed to the evolution of the Brazilian economy.